Analysis of RANKL Expression Following Ethanol Administration During Orthodontic Force Application: An In Vivo Study - Rehatta, Dwayne Daniel Fredrick (2025)
The prevalence of alcohol consumption is still quite high in worldwide. As more people become aware of malocclusion, it is also reasonable to expect that some orthodontic patients drink alcohol. Impacts of alcohol (ethanol) consumption on orthodontic force still unclear.  Analyze the differences and effects of ethanol on RANKL expression in bone remodeling process during application of orthodontic force. This research was in vivo study, involving twenty-five Wistar rats, fitted with a closed coil spring and then divided into 5 groups; negative control group A (without force and ethanol) on day 0; group K1 (K=given orthodontic force) on day-3 and K2 on day-14, and group P1 (P=given force and 20% ethanol) on day-3 and P2 on day-14. Furthermore, animals were sacrificed, preparations were made and Immunohistochemistry (IHC) was examined to calculate RANKL expression, then data analysis using independent-t and regression test.  Independent sample t-test showed, K and P group had significantly differences of RANKL expression on day 3 and 14 (p<0,05). Regression test results showed duration of ethanol administration significantly affected the level of RANKL expression (p<0,05).  There were  differences in RANKL expression after alcohol administration and there were  effects of ethanol on RANKL expression in bone remodeling process during application of orthodontic force. It’s speculated that ethanol increases osteoclastogenesis, which accelerates orthodontic movement, but more study required.